Influence of Fatty Infiltration on Hip Abductor Repair Outcomes: A Systematic Review and Meta-analysis. Issue 9 (July 2022) - Looney, Austin M.; Bodendorfer, Blake M.; Donaldson, Stiles T.; Browning, Robert B.; Chahla, Jorge A.; Nho, Shane J.
Background: Increasing evidence supports surgical intervention for hip abductor tears; however, the influence of fatty infiltration (FI) on outcomes after repair remains uncertain and has been addressed only in small case series. Purpose: To clarify the relationship between FI and surgical outcomes for hip abductor tears. Study Design: Meta-analysis; Level of evidence, 4. Methods: A systematic review and meta-analysis was conducted according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. FI severity was assessed by Goutallier-Fuchs (G-F) grade. The relationship between FI and improvement in Harris Hip Score (HHS)/modified Harris Hip Score (mHHS) and visual analog scale (VAS) score for pain was examined with mixed-effects metaregression. Outcomes with open and endoscopic techniques were also compared. Results: A total of 4 studies (206 repairs in 201 patients) were eligible. High-grade FI was associated with significantly less improvement in HHS/mHHS than both no FI (6.761 less; 95% CI, 3.983-11.570; P = .002) and low-grade FI (7.776 less; 95% CI, 2.460-11.062; P < .001) but did not significantly influence VAS score ( P > .05). Controlling for FI severity, we found no significant difference in HHS/mHHS improvement between open versus endoscopic repair ( P > .05 at each level), but open repair resulted in significantly greater improvement in VAS score for every G-F grade (all P < .005). Conclusion: Surgical intervention for symptomatic hip abductor tendon tears improved outcomes as reflected by change in HHS/mHHS; however, the presence of high-grade FI resulted in less improvement. FI severity did not influence VAS scores for pain. Although no differences were found between open and endoscopic repairs in terms of FI-adjusted improvement in HHS/mHHS, open repairs resulted in significantly greater pain relief at each FI level.